The Effect of TGfU and Conventional Physical Learning on Object Control of Elementary School Students - Oktofanny, William; Bakhtiar, Syahrial; Emral, Emral; Khairuddin, Khairuddin; Munir, Ali; Zarya, Fiky (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
This study is to see the difference in the influence of providing learning programs that use teaching games for understanding and conventional methods in physical education learning on students' abilities in mastering Object Control. This type of research is quantitative associative with a quasi-experimental approach. The design of this study is a 2x2 factorial design. The population in this study was all students of SDN 52/V Pematang Pauh, Tanjung Jabung Barat Regency, Jambi Province, totaling 264 people. Samples were taken using probability sampling, which was divided using simple random sampling totaling 18 male students and 14 female students, then grouped using matching ordinal pairing. The research instrument uses the Test of Gross Motor Skill-2. Data were analyzed by path analysis through 2-path AVAVA testing at α=0.05. The results of hypothesis testing show: (1) There are differences in the level of ability of control objects based on the provision of learning methods where it is found that in the table of hypothesis test results in the method row a significance value of 0.047 is obtained, (2) There are differences in the level of ability of control objects based on sex differences where found in the table of hypothesis test results in the sex row a significance value of 0.002 is obtained, (3) There is no interaction between learning methods and gender in determining the level of ability of control objects where in the table of hypothesis test results in the method row *gender obtained a significance value of 0.740. So it can be concluded that the learning method provided affects the ability of student control objects. The learning method and gender each influence the ability of the object of control but do not affect each other, so it could be that girls and boys with the same method have the same improvement.